Analysis Autocorrelation Spatial on Amount Fundraising at LAZISMU Semarang City Using Moran's Index: Analisis Autokorelasi Spasial pada Jumlah Penghimpunan Dana di LAZISMU Kota Semarang Menggunakan Indeks Moran - Choirunnisa Hasna Nisa; Khansa' Ni'mal 'Abidah; M. Al Haris; Fatkhurokhman Fauzi (Department of Sains Data UNIMUS Universitas Muhammadiyah Semarang, 2025)
Institution Zakat and Infaq Collectors And Sed e kah Muhammadiyah (LAZISMU) , has role important in gather And distribute funds activity social use help communities in need . L AZISMU Semarang City in general special focus on management funds at the level city , with not quite enough answer gather And allocate funds from public to humanitarian programs like help education , health , and help social research​ This aim For increase effectiveness collection funds Institution Zakat, Infaq , and Charity Collectors Alms Muhammadiyah in Semarang City. With apply approach spatial , research This analyze pattern distribution geographical donors , potential donations , and characteristics economy as well as demographics in each sub-district . Methodology study involving spatial data collection and analysis statistics . Results study This expected can give contribution on understanding scientific related zakat- based management spatial And become guidelines for institution similar in optimize collection And allocation funds .